Von Menschen, Maschinen und dem Minimalen : musikanalytische Überlegungen zum Techno-Projekt The Brandt Brauer Frick Ensemble - Schaubruch, Josef; Justus Liebig University Giessen (My University, 2016)
Although Electronic Dance Music (EDM) ranks among one of the most popular styles in the 21st century, the academic debate about the distinct musical qualities of EDM is sparse. The article transfers the theoretical framework developed by Mark Butler (2006) to the music of the Berlin based techno collective The Brandt Brauer Frick Ensemble who create music with an EDM aesthetic by using instruments played live out of a score. The focus of the analysis is on rhythm, meter, and form. Finally, the article illuminates not only an unexplored field of producing techno in an uncommon way, it also provides an enlightening insight into the specific applicability of Butler´s analytical tools.
Keywords: ddc:780